Calcifying Ghost Cell Odontogenic Cyst: Report of a Case and Review of Literature - Archana Sonone; V. S. Sabane; Rajeev Desai (Case Reports in Dentistry)
The calcifying ghost cell odontogenic cyst (CGCOC) was first described by Gorlin et al. in 1962. Calcifying ghost cell odontogenic cyst is comparatively rare in occurrence, constituting about 0.37% to 2.1% of all odontogenic tumors. The most notable features of this pathologic entity are histopathological features which include a cystic lining demonstrating characteristic “Ghost” epithelial cells with a propensity to calcify. In addition, the CGCOC may be associated with other recognized odontogenic tumors, most commonly odontomas. There are variants of CGCOC according to clinical, histopathological, and radiological characteristics. Therefore a proper categorization of the cases is needed for better understanding of the pathogenesis of each variant. Here, we report a classical case of calcifying odontogenic cyst along with a brief review of literature.